Potential chemoprevention of primary liver cancer using optimized formulation of Strobilanthus crispus (L.) blume and Centella asiatica L. juices - Hussin, Faridah (2011)
This study was conducted to evaluate the chemoprevention potential of Strobilanthes crispus and Centella asiatica juices on liver cancer cell line (HepG2). The first and second parts of the study were on the optimization of juices formulation and processing condition for the development of high quality juices using response surface methodology. The combined effect of two independent variables for formulation optimization i.e. herbal puree (14-24%) and honey (14-40%), and two independent variables for processing condition i.e. temperature (60-800 C) and time (8-30 min) were studied. Response surface plots showed increase in herbal and honey concentration, temperature and time of processing reduced the response variables significantly (p < 0.05). The optimum product formulation for Centella asiatica and Strobilanthes crispus juices singly were 14% of both herb and honey concentration. The optimum parameter for processing of Centella asiatica juice was at 70°C for 8 min whereas the optimum parameter for processing of Strobilanthes crispus juice was at 69°C for 8 min. The third part of the study focused on the cytotoxic activities of juices at different concentration (0.001, 0.01, 0.1, 1 and 10%) and incubation time (24, 48, 72 hours). MTT (3-(4, 5-dimethylthiazole-2yl)-2, 5-diphenyl tetrazolium bromide) assay was used to examine the cytotoxic effect of juices on Chang cell line as control and HepG2 cells. Increasing doses of both juices up to 10% had no cytotoxic effect against Chang cell line as indicated by absence of IC50 values when the cell lines were treated for up to 72 hours incubation time. However, Strobilanthes crispus juice and Centella asiatica juice inhibited the proliferation of HepG2 cancer cell lines in a concentration-dependent manner as well as exposure time. The cytotoxicity started at a concentration as low as 0.1% for both juices. At 72 hours incubation time, Strobilanthes crispus and Centella asiatica juice showed cytotoxicity effects with an IC50 of approximately 0.4 (4 mg/L) and 0.1% (1 mg/L) respectively. The fourth part of this study was to discuss on the apoptotic morphology of HepG2 cancer cells treated with both juices by quantitatively measuring the apoptotic cell percentage using flow cytometry and comet assay. Both juices induced apoptosis in a dosedependent manner after being exposed to HepG2 cell lines for 72hr. At more than 0.1% concentration of juices, both Centella asiatica and Strobilanthes crispus showed higher percentage of apoptotic cell death (sub-GI population) than the control HepG2 cells. Comet assay also showed that all cells exhibited a dose-dependent increase in DNA damage compared to controls. A significant induction of DNA damage was seen at concentrations of above 0.1% for both juices. Finally the last part of the study was to observe the changes in the c-myc, c-fos and cerbB2 oncogenes expression induced by the Centella asiatica and Strobilanthes crispus juices. Results revealed that Centella asiatica juice reduced level of c-myc but increased level of c-fos and c-erbB2 expression on HepG2 cells. Contrary, Strobilanthes crispus juices showed increased level of c-myc with reduced level of c-fos and c-erbB2 expression on HepG2 cells. In conclusion, Centella asiatica and Strobilanthes crispus juices have potential as chemopreventive agents in liver cancer cell.